Do Market-wide Circuit Breakers Effectively Reduce the Volatility? Evidence from China Stock Market Micro-structure - Guo, Yumeng (2020)
The circuit breaker mechanism was first installed in China stock market on January 4, 2016 but triggered four times and abandoned just in 4 trading days, leading to huge panic and abnormal fluctuation. Existing literature argues that the circuit breakers may not be able to reduce volatility but accelerate the market toward to the thresholds when it moves to the limits at the same direction (The magnet effect). This study investigates the impacts of the circuit breakers in China stock market and test the effectiveness using high frequency intraday data, regarding CSI300 index as the benchmark. The AR(2)-GARCH(1,1) model is established to empirically measure the volatility changes as well as magnet effects of circuit breakers. Besides, the study further analyzes the different micro characteristics of the magnet effect in both rising and falling stages before and after the launch of circuit breakers. A asymmetric test through the adjusted TARCH model on the basis of GARCH is also carried out carefully, which might fills the gap in the literature of the different performance of the market when facing positive information and negative shock in China. The empirical results show that the market tended to be much more volatile during the time when the circuit breakers were introduced. Secondly, the magnet effect exists not only in a downward stage but also in a upward stage, which is reflected that the CSI300 index always moves toward the boundaries when it is close to the breakpoints. It is also concluded that the intensity of the magnet effect varies under different levels of threshold settings and different movement trends. Last but not least, markets are more easily affected by some negative shocks such as more stringent regulations or trading limits, instead of positive impacts.